2019
DOI: 10.1159/000494885
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Long-Term Stroke Mortality, Recurrence and Disability in Iran: The Mashhad Stroke Incidence Study

Abstract: <b><i>Background:</i></b> Little is known about the association between socioeconomic status and long-term stroke outcomes, particularly in low- and middle-income countries. <b><i>Methods:</i></b> Patients were recruited from the Mashhad Stroke Incidence Study in Iran. We identified different socioeconomic variables including the level of education, occupation, household size, and family income. Residential location according to patient’s neighbourhood was classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Nonetheless, it is understood that unemployment is an important factor in stroke mortality. Similarly, Morovatdar et al found that unemployment prior to stroke was associated with an increased risk of 1-and 5-year post-stroke mortality, 35 which is consistent with our result. The pressure of excessive work and stress related to hard work and even unemployment can probably be the causes of stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, it is understood that unemployment is an important factor in stroke mortality. Similarly, Morovatdar et al found that unemployment prior to stroke was associated with an increased risk of 1-and 5-year post-stroke mortality, 35 which is consistent with our result. The pressure of excessive work and stress related to hard work and even unemployment can probably be the causes of stroke.…”
Section: Discussionsupporting
confidence: 92%
“…A higher rate of stroke with poor outcomes in our study may be explained by differences in the rate of vascular risk factors [16] and etiology of stroke in our population [21, 22]. In addition, socioeconomic disadvantage [23], unhealthy lifestyle [24], and different socioeconomic variables [25], including high-risk behaviors (e.g., SUD), may be associated with stroke incidence and outcomes. The current study was designed to assess the association between SUD and long-term outcomes of stroke, including mortality, stroke recurrence, disability, and functional dependency.…”
Section: Introductionmentioning
confidence: 88%
“…We defined disability as an mRS of > 2 and functional dependency as a BI of < 60 [19]. According to the patients’ neighborhood, patients were categorized into 3 subgroups: less privileged area, middle privileged area, and high privileged area [23]. As a part of our clinical assessments, trained nurses and medical students at the residency level had a face-to-face interview regarding SUD, including opioids (burned and the sap), hashish, or similar compounds, heroin, amphetamine-type stimulants, hallucinogens, naswar (a mixture of tobacco and slaked lime, usually with some flavors such as indigo and juniper ash), and inhalants.…”
Section: Methodsmentioning
confidence: 99%
“…The SES has a significant impact on the physiological decline process of the older adults [ 30 ], but this effect is bidirectional, which leads to the uncertainty of the final consequence. On the one hand, it can vary the changing process of self-care ability and reduce the risk of ADL disability of the older adults through many factors, such as the material conditions of individual survival, the access of care services and living environment [ 31 , 32 ]. On the other hand, social and economic resources can provide support for the disabled older adults and prolong their survival time [ 33 , 34 ].…”
Section: Theory and Hypothesismentioning
confidence: 99%